Effect of caffeine on pneumogram and apnoea of infancy. Issue 9 (September 1986) - Anwar, M; Mondestin, H; Mojica, N; Novo, R; Graff, M; Hiatt, M; Hegyi, T
Abstract : We studied the efficacy of caffeine in improving pneumogram abnormalities and relieving clinically important apnoea of infancy in 23 infants. After obtaining a 12 hour pneumogram we administered caffeine citrate in a loading dose of 20 mg/kg followed by 5 mg/kg once daily. This dose achieved a trough caffeine blood concentration of 9.6 (SD 2.0) micrograms/ml. A repeat pneumogram performed seven to 10 days after the first pneumogram showed a significant reduction in the number of short and prolonged attacks of apnoea as well as in the per cent periodic breathing and apnoea density. Episodes of prolonged apnoea disappeared in all infants after administration of caffeine and in 11 infants all pneumogram abnormalities resolved. This improvement in the results of pneumograms was associated with resolution of clinically important apnoea requiring intervention. Caffeine was administered for 3.4 (SD 1.3) months and was well tolerated by all except two infants. We conclude that treatment with caffeine is helpful in preventing attacks of apnoea that require intervention, and improvement in the results of pneumograms after administration of caffeine predicts this favourable response.